Towards a Natural History of Soil Bacterial Communities. Issue 4 (April 2018) - Martiny, Jennifer B.H.; Walters, Kendra E.
Abstract : Despite the enormous diversity of bacteria, a recent study reveals that soils are globally dominated by a small list of taxa. Characterizing the traits of these bacteria offers the potential for predicting functional differences among soil communities.